2004
DOI: 10.1021/bi049262u
|View full text |Cite
|
Sign up to set email alerts
|

Low Concentrations of Sodium Dodecyl Sulfate Induce the Extension of β2-Microglobulin-Related Amyloid Fibrils at a Neutral pH

Abstract: In beta(2)-microglobulin-related (Abeta2M) amyloidosis, partial unfolding of beta(2)-microglobulin (beta2-m) is believed to be prerequisite to its assembly into Abeta2M amyloid fibrils in vivo. Although low pH or 2,2,2-trifluoroethanol at a low concentration has been reported to induce partial unfolding of beta2-m and subsequent amyloid fibril formation in vitro, factors that induce them under near physiological conditions have not been determined. Using fluorescence spectroscopy with thioflavin T, circular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
221
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(232 citation statements)
references
References 43 publications
11
221
0
Order By: Relevance
“…On the other hand, recent findings by Yamamoto et al (14) and Kihara et al (15) suggest that the extensive fibril formation under physiological conditions can be reproduced under certain conditions such as in the presence of 0.5 mM SDS. Here, we examined the effects of ultrasonication on monomeric ␤2-m at pH 7.0 in the presence of 0.5 mM SDS.…”
Section: Ultrasonication-induced Fibrilmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, recent findings by Yamamoto et al (14) and Kihara et al (15) suggest that the extensive fibril formation under physiological conditions can be reproduced under certain conditions such as in the presence of 0.5 mM SDS. Here, we examined the effects of ultrasonication on monomeric ␤2-m at pH 7.0 in the presence of 0.5 mM SDS.…”
Section: Ultrasonication-induced Fibrilmentioning
confidence: 93%
“…In contrast, the generation of a substantial amount of amyloid fibrils at neutral pH has been difficult (see below). Recently, Yamamoto et al (14) found that low concentrations of SDS, around the critical micelle concentration (0.7 mM), not only stabilize fibrils but also induce extensive growth of ␤2-m amyloid fibrils at neutral pH. Moreover, Kihara et al (15) found that repeated self-seeding at pH 7.0 with fibrils formed at the same pH results in an acceleration of fibril growth, approaching the phenomenon that occurs under physiological conditions.…”
mentioning
confidence: 99%
“…ThT Fluorescence Assay-ThT specifically binds to amyloid fibrils and consequently produce enhanced light emission (18,31,32). The formation of amyloid fibrils was monitored with the ThT fluorescence assay using a microplate (Greiner bio-one 96-well microplate 675-074, made of polystyrene) and a microplate reader (MTP-810, Corona Electric Co., Ibaraki, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Thioflavin T forms a complex with fibrils, and the fluorescence intensity is proportional to the amount of fibrils that are present when the concentration of ThT is held constant (16). The effects of ThT buffer solutions on LC structure were evaluated by circular dichroism (CD) and confirmed by TEM and AFM (27)(28)(29)(30).…”
Section: Methodsmentioning
confidence: 99%